Nuclear risk perception, political efficacy, and Internet use for civic engagement in China. Issue 2 (3rd April 2018) - Qiu, Hongfeng; Weng, Suwei; Du, Kaijian
Abstract : Nuclear power was recently reintroduced into China's economic agenda. However, concerns have arisen as to how communities close to the sites of newly planned nuclear power plants react to the potential environmental and health risks. In a field study conducted in the proximity of the Yunxiao Nuclear Power Plant in Fujian province, it was discovered that a majority of the respondents perceived the project as having a certain level of risk. Nevertheless, online social networks were rarely used to seek relevant information, discuss benefits and threats, deliver concerns to decision-makers, or even to mobilize collective actions. Further investigation revealed a strong connection between the political efficacy of the respondents and their level of Internet use for civic engagement. The mechanisms underlying the formation of political efficacy are examined by relating the discourses of risk to their social contexts.